A nanofilm‐based fluorescent sensor for determination and identification of gas‐phase alkylamine - Jiahui Hu; Xiangquan Liu; Hexi Wei; Rongrong Huang; Binbin Zhai; Yan Luo; Junbao Yan; Lingya Peng; Mei Liu; Yu Fang (Responsive Materials)
Abstract On‐site and real‐time detection and identification of alkylamines are important, but remain as a challenge. In this work, we report a unique nanofilm and the nanofilm‐based high‐performance fluorescent alkylamine sensor. The nanofilm was prepared at the air/dimethyl sulfoxide interface with 4,4′,4″‐nitrilo‐tribenzohydrazide (TPATH) and 4,7‐diphenylaldehyde‐benzothiadiazole (BT‐2CHO) as the building blocks, and depicted self‐standing, defect‐free, fluorescence active, and superior adhesive properties, enabling fabrication of a robust fluorescence film sensor. The response time of the sensor to the tested alkylamines is within 0.2 s, and the detection limits for butylamine, dimethylamine and triethylamine are 4, 8 and 70 ppm, respectively. Moreover, the profiles of the fluorescence emission spectra of the nanofilm recorded after exposure to alkylamines of primary, secondary, and tertiary structures are different from one to another, enabling discrimination of them. The diversified response behavior and the related identification property of the sensor to the different alkylamines was ascribed to the formation of different complexes between the analytes and the nanofilm. The high performance of the BT‐TPATH nanofilm‐based alkylamine sensor may guarantee its application in disease diagnosis, food spoilage monitoring, environmental monitoring, etc.